Fighting back - women's resistance to rape - Ullman, S. E. (Journal of interpersonal violence, 1992)
Women's resistance strategies to rape were examined using police reports and the court testimonies of 274 women who either avoided rape or were raped by subsequently incarcerated sex offenders. The sequence of behaviors in the offender-victim interaction was analyzed to determine whether women who resist rape with physical force are, as some have suggested, exacerbating the potential for physical injury or are simply responding to the severity of the offender's physical attack. The results indicated that 85% of the women in the study who resisted with physical force did so in response to the offender's initiated violence. The remaining 15% who resisted with physical force did so in response to the offender's verbal aggression. Moreover, those women who responded with physical aggression to the offender's violent physical attack were more likely to avoid rape than were women who did not resist such force. Also, the potential for physical injury was no greater for these women than for those who used other resistance strategies or who offered no resistance. These analyses suggest that the frequently found correlation between physical resistance and injury of the woman might be the result of the initial level of the offender's violence and should not be used to discourage women from physically resisting rape